A Knowledge, Attitudes and Practices Survey Conducted Three Years after Halting Ivermectin Mass Treatment for Onchocerciasis in Guatemala. - Frank O Richards; Robert E Klein; Oscar de León; Renata Mendizábal-Cabrera; Alba Lucía Morales; Vitaliano Cama; Carol G Crovella; Carlos E Díaz Espinoza; Zoraida Morales; Mauricio Sauerbrey; Nidia Rizzo (Public Library of Science (PLoS), 2016)
BACKGROUND:Mass drug administration (MDA) with ivermectin for onchocerciasis was provided in Guatemala's Central Endemic Zone (CEZ) over a 24 year period (1988-2011). Elimination of Onchocerca volvulus transmission was declared in 2015 after a three year post MDA surveillance period (2012-2014) showed no evidence of recrudescence. The purpose of the present study was to evaluate the knowledge, attitudes and practices (KAP) towards onchocerciasis and ivermectin among residents in the post endemic CEZ. A major interest in this study was to determine what community residents thought about the end of the ivermectin MDA program. METHODOLOGY/PRINCIPAL FINDINGS:A total of 148 interviews were conducted in November 2014 in four formerly hyperendemic communities using a standard questionnaire on smart phones. The majority (69%) of respondents knew that the MDA program had ended because the disease was no longer present in their communities, but a slight majority (53%) was personally unsure that onchocerciasis had really been eliminated. Sixty-three percent wanted to continue to receive ivermectin because of this uncertainty, or because ivermectin is effective against intestinal worms. Eighty-nine percent of respondents said that they would seek medical attention immediately if a family member had symptoms of onchocerciasis (especially the presence of a nodule), which is a finding very important for ongoing surveillance. CONCLUSIONS/SIGNIFICANCE:Many respondents wanted to continue receive ivermectin and more than half did not believe onchocerciasis had been eliminated. The ministry of health outreach services should be prepared to address ongoing concerns about onchocerciasis in the post endemic CEZ.